Indigofera yuanjiangensis (Fabaceae: Papilionoideae), a new species from Yunnan, China - Zhao, Xue-Li; Jiang, Li-Sha; Gao, Xin-Fen (Phytotaxa, 2020)
Indigofera yuanjiangensis X.F. Gao & Xue Li Zhao (Fabaceae), a new species from Yunnan, China, is described and illustrated. Information about its distribution, habitat, and phenology is also provided. The species is morphologically similar to I. megaphylla, I. esquirolii and I. sticta, but they differ in the leaf length, leaflet number, leaflet size, raceme length, flower color and standard size.